124I Radiolabeling of a AuIII‐NHC Complex for In Vivo Biodistribution Studies. Issue 39 (29th July 2020) - Guarra, Federica; Terenzi, Alessio; Pirker, Christine; Passannante, Rossana; Baier, Dina; Zangrando, Ennio; Gómez‐Vallejo, Vanessa; Biver, Tarita; Gabbiani, Chiara; Berger, Walter; Llop, Jordi; Salassa, Luca
Abstract: Au III complexes with N‐heterocyclic carbene (NHC) ligands have shown remarkable potential as anticancer agents, yet their fate in vivo has not been thoroughly examined and understood. Reported herein is the synthesis of new Au III ‐NHC complexes by direct oxidation with radioactive [ 124 I]I2 as a valuable strategy to monitor the in vivo biodistribution of this class of compounds using positron emission tomography (PET). While in vitro analyses provide direct evidence for the importance of Au III ‐to‐Au I reduction to achieve full anticancer activity, in vivo studies reveal that a fraction of the Au III ‐NHC prodrug is not immediately reduced after administration but able to reach the major organs before metabolic activation. Abstract : Images : The reaction of [ 124/131 I]I2 with Au I ‐N‐heterocyclic carbene precursors affords a strategy to label Au III anticancer agents and study their biodistribution in vivo by positron emission tomography.